Relevansi Terminologi Struktur Masyarakat Aceh Terhadap Warna Kebangsaan Indonesia - Teguh Santoso (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
Terminology is one of Linguistics fields. With regard to this, there are many linguistic data related to theterminology. One of Indonesian terminologies in terms of social structure can be found in Aceh province. The Acehnese structure is divided into the highest level to the lowest level. These structural levels are known asmukim, gampong, sagoe, etc. The terminology can be optimized in terms of contributing to the color of Indonesian nationality. Accordingly, the unity in diversity is not abondoning the roots of local culture.